Working memory load modulates the processing of audiovisual distractors: A behavioral and event-related potentials study - Yuan, Yichen; He, Xiang; Yue, Zhenzhu (Frontiers in Integrative Neuroscience, 2023)
The interplay between different modalities can help to perceive stimuli more effectively. However, very few studies have focused on how multisensory distractors affect task performance. By adopting behavioral and event-related potentials (ERPs) techniques, the present study examined whether multisensory audiovisual distractors could attract attention more effectively than unisensory distractors. Moreover, we explored whether such a process was modulated by working memory load. Across three experiments, n-back tasks (1-back and 2-back) were adopted with peripheral auditory, visual, or audiovisual distractors. Visual and auditory distractors were white discs and pure tones (Experiments 1 and 2), pictures and sounds of animals (Experiment 3), respectively. Behavioral results in Experiment 1 showed a significant interference effect under high working memory load but not under low load condition. The responses to central letters with audiovisual distractors were significantly slower than those to letters without distractors, while no significant difference was found between unisensory distractor and without distractor conditions. Similarly, ERP results in Experiments 2 and 3 showed that there existed an integration only under high load condition. That is, an early integration for simple audiovisual distractors (240–340 ms) and a late integration for complex audiovisual distractors (440–600 ms). These findings suggest that multisensory distractors can be integrated and effectively attract attention away from the main task, i.e., interference effect. Moreover, this effect is pronounced only under high working memory load condition.